Sayyid Qutb's understanding of 'aqidah : an analysis - Abdul Halim Syihab (Kulliyyah of Islamic Revealed Knowledge, International Islamic University Malaysia, 2007)
'Aqidah plays a vital role in shaping Muslim thought and behaviour. It is the first element that guides to the real meaning of this life and interprets its past, present and future. Sayyid Qutb never neglected this point in his writings. Rather, he placed significant importance by innovating his own understanding based on his wide knowledge and experiences. His magnificent work, Fi Zilal al-Qur'an is one of the most recognized contemporary Qur'anic exegesis that reflects his views on matters related to Tawhid al-Uluhiyyah, al-Rububiyyah, al-Sifat and many more. Based on the above mentioned fact, this research aims to examine Sayyid Qutb’s understanding of 'Aqidah and explore the truth whether it is in line with the early Muslim scholars or not, under the title; Sayyid Qutb’s Understanding of 'Aqidah: An Analysis. It wishes to answer several issues and questions with regards to his thought such as did he rely on authentic sources of the Qur'an and Hadith while formulating his interpretations or not and did he actually disparage any of the companions or scholars before him. If he did not, what was his justification to his oppositions and did he really harbour leaning towards destructive schools (al-firaq al-haddamah). The researcher will employ a library based research. He will study books by Sayyid Qutb on the issues of 'Aqidah in order to explore his understanding and interpretation. The researcher will consult books written on him as well as journals and articles in the internet as to further evaluate his approaches on comprehending the contemporary issues of 'aqidah. The researcher will explore his magnum opus Fi Zilal al-Qur'an and his key work Khasa'is al-Tasawwur al-Islami wa Muqowwimatuhu to explore his understanding in explaining the matters related to 'aqidah. Other books will also be referred to as to make it factually comprehensive. This methodology will be utilized on this research for clarifying the following issues; Sayyid Qutb’s literary endeavour and historical involvement with the Ikhwan al-Muslimin, his attitude toward early Muslim, his understanding and interpretation to the matter of Tawhid, the concept of Islamic and Jahiliyyah society, the employment of Hadith Ahad in the matter of 'aqidah, his interpretation of Sifat, his philosophical views, the discourse of human reasoning and the concept of Dar al-Islam and Dar al-Harb. This research will highlight all the accusations addressed to Sayyid Qutb due to his thought and find out whether they all true or not. This research will explore in detail about Sayyid Qutb’s understanding of ‘aqidah and answers all raised issues scientifically based on authentic sources.